2022
DOI: 10.1038/s41598-022-11439-7
|View full text |Cite
|
Sign up to set email alerts
|

Excretion and viability of SARS-CoV-2 in feces and its association with the clinical outcome of COVID-19

Abstract: The main objective was to evaluate the viability of the SARS-CoV-2 viral particles excreted in stools. In addition, we aimed to identify clinical factors associated with the detection of SARS-CoV-2 RNA in feces, and to determine if its presence is associated with an unfavorable clinical outcome, defined as intensive care unit (ICU) admission and/or death. A prospective multicenter cohort study of COVID-19 adult patients, with confirmed SARS-CoV-2 infection by RT-PCR assay in nasopharyngeal (NP) swabs admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 15 publications
3
36
0
2
Order By: Relevance
“…To further validate this finding, we carried out Western blot and RT-PCR analysis on the plant sap extracted from individual leaves, and CPMV could not be detected, neither on the protein nor at the RNA level (Figure B,C), which suggests that the RNA detected in stool may not be infectious toward plants. This is congruent with data surrounding SARS-CoV-2, where viral RNA with a mitigated replicative capacity can be detected in stool samples …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…To further validate this finding, we carried out Western blot and RT-PCR analysis on the plant sap extracted from individual leaves, and CPMV could not be detected, neither on the protein nor at the RNA level (Figure B,C), which suggests that the RNA detected in stool may not be infectious toward plants. This is congruent with data surrounding SARS-CoV-2, where viral RNA with a mitigated replicative capacity can be detected in stool samples …”
Section: Resultssupporting
confidence: 89%
“…This is congruent with data surrounding SARS-CoV-2, where viral RNA with a mitigated replicative capacity can be detected in stool samples. 74 From a translational perspective, these data convey that shedding of infectious CPMV was not evident after I.T. or oral dosing.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to a few existing examples in the literature ( Rimoldi et al, 2020 , Westhaus et al, 2021 ), no endogenous infectious SARS-CoV-2 was detected in the wastewater samples collected for this study. These results indicate that SARS-CoV-2 is either quickly inactivated in wastewater, irreversibly adheres to wastewater particulates, or as recent studies have suggested, infected individuals do not excrete detectable infectious virus in their stool (2001, 2001; Ahmed et al, 2020b ; Albert et al, 2021 ; Carducci et al, 2020 ; Cerrada-Romero et al, 2022 ; Tiwari et al, 2021 ). Taken together, these findings suggest the need to further understand the feasibility and importance of monitoring infectious SARS-CoV-2 in environmental matrices (e.g., wastewater).…”
Section: Discussionmentioning
confidence: 52%
“…Despite SARS-CoV-2 RNA being detected in stools, and the persistent viral shedding of SARS-CoV-2 in feces, current data from different studies are conflicting regarding the detection of infectious particles in feces. Infectious viral particles may be retrieved from anecdotal cases, although studies indicate that the vast majority of individuals infected with SARS-CoV-2 do not release infectious particles from stools [ 125 ]. While high viral RNA concentrations were observed in stools in two different studies (9 and 10 patients, respectively), infectious virus was not recovered in those samples [ 33 , 125 , 126 ].…”
Section: Current Insights Research Needs and Potential Impact On Clin...mentioning
confidence: 99%
“…Infectious viral particles may be retrieved from anecdotal cases, although studies indicate that the vast majority of individuals infected with SARS-CoV-2 do not release infectious particles from stools [ 125 ]. While high viral RNA concentrations were observed in stools in two different studies (9 and 10 patients, respectively), infectious virus was not recovered in those samples [ 33 , 125 , 126 ]. In contrast, replicating SARS-CoV-2 virus was detected in feces in [ 127 ] and viable SARS-CoV-2 particles in stool samples in [ 128 ].…”
Section: Current Insights Research Needs and Potential Impact On Clin...mentioning
confidence: 99%